RECOGNIZING CORRELATED PATTERNS FROM REMOTELY SENSED IMAGES: A NEW LEARNING RULE BASED ON SPIN GLASS THEORY - Krishnan R.; Vijendran V.G. (My University, 2001)
Classification of remotely sensed images is a rich research field wherein techniques from conventional statistics to recent developments such as Artificial Neural Network, Fuzzy logic etc. has wide applications. Conventionally remotely sensed image classification referred to pixel classification based on broad categories such as vegetation and water bodies. With the availability of high-resolution imageries, shape analysis of macro structures contained in images becomes an important and difficult task. Although conventional statistical pattern recognition techniques give a reasonable result, Artificial neural network methods seem to be giving better results. In this paper, we give a survey of feed-forward neural network used for shape classification and a Hopfield model with an improved learning rule, for a typical shape analysis problem.
Keywords: BACK PROPAGATION MODEL; HOPFIELD MODEL; SPIN GLASS MODEL